Changes in activity of metalloproteinases 2 and 9 in rat liver in experimental model of cholestasis taking into account its duration and assessment of selected features - Krzysztof Suszyński; Natalia Białoń; Dariusz Górka; Anna Dolińska; Mikołaj Górka (Śląski Uniwersytet Medyczny w Katowicach, 2023)
INTRODUCTION: Cholestasis, otherwise known as bile stasis, occurs when the flow of bile is blocked. There are currently two types of cholestasis: extrahepatic and intrahepatic. The factors causing cholestasis include alcoholic and non-alcoholic fatty liver disease, infections, biliary tract disease, biliary tract tumours or pancreatic disease. The aim of this study was to assess the features of cholestasis and changes in the activity of metalloproteinases 2 and 9. MATERIAL AND METHODS: The study material consisted of 36 male rats of the Sprague-Dawley strain weighing 350-420 g. The animals were divided into 3 study groups and 3 control groups, each with 6 animals. An extrahepatic cholestasis model was induced in the study groups. In both groups, the animals were reoperated on consecutively after 3, 7 and 14 days. The activity of the selected metalloproteinases was assessed by zymography. The histopathological preparations were then assessed microscopically, evaluating the characteristic features of cholestasis in rat liver. RESULTS: All the groups were statistically analysed using the Kruskal-Wallis test for non-parametric values. Computerised densitometric analysis of the zymography results obtained from the collected material showed the presence of MMP-2 and MMP-9 activity. Statistically significant differences were determined for MMP-2, where its activity was found to be elevated in groups I C, III C (*p < 0.05) compared to the control groups. An increasing trend was observed. CONCLUSIONS: MMP-2 activity increases with the duration of cholestasis. The results of the histopathological analysis of selected features of cholestasis showed that significantly higher scores were obtained by the animals in the experimental cholestasis model.